Analysis of Work Environment, Work Motivation, and Job Training on Work Productivity at PT OCS Global Services - Sindi W. Berampu; Darmilisani Darmilisani (UNIVED Press, 2025)
This study analyzes the influence of the work environment, work motivation, and job training on employee productivity at PT OCS Global Services. The research employs a quantitative approach using multiple regression analysis. Data were collected through questionnaires distributed to 71 respondents. The findings of this study indicate that: (1) The work environment has a positive and significant effect on work productivity (t-value 3.549 > t-table 1.996; sig. 0.001); (2) Work motivation has a positive and significant effect on work productivity (t-value 3.046 > t-table 1.996; sig. 0.005); (3) Job training has a positive and significant effect on work productivity (t-value 2.751 > t-table 1.996; sig. 0.011); (4) Collectively, the three independent variables have a positive and significant effect on work productivity (F-value 14.697 > F-table 2.74; sig. 0.000), with a contribution of 62.9% (R² = 0.629). The study concludes that the work environment, work motivation, and job training are significant factors in improving employee productivity at PT OCS Global Services. It is recommended that the company enhance educational and employee development opportunities, optimize continuous training programs, and effectively utilize work experience through performance evaluations and an appropriate reward system.